Palm Oil-Derived Phytosterol: Glutathione Antioxidant Status in Rats Exposed to Carbon Tetrachloride - Mohd Fahami Nur Azlina, Haji Mohd Saad Qodriyah, Mohamed Norazlina, Yusof Kamisah, Ahmad Shuid Nazrun, Marzuki Alini (Journal of Applied Pharmaceutical Science, 2016)
The aim of this study was to assess the antioxidant effect of phytosterol from palm oil by studying its ability to improve antioxidant status of rats induced with oxidative stress by carbon tetrachloride (CCl4). The rats were divided into four groups of normal control (NC), carbon tetrachloride (CCl4), phytosterol (P) and phytosterol plus carbon tetrachloride (P+CCl4). The P and P+CCl4 groups received weekly phytosterol pre-treatment via subcutaneous injections at 140 mg/kg rat weight for 5 weeks while the NC and CCl4 groups only received olive oil (vehicle). Carbon tetrachloride at the dose determined by a preliminary study was given as single oral dose to induce lipid peroxidation in the CCl4 and P+CCl4 groups. After 24 hours, the rats were sacrificed and the heart, liver, kidney and lung were isolated for the determination of reduced glutathione (GSH) and oxidized glutathione (GSSG) levels. Carbon tetrachloride caused significant reduction in the GSH:GSSH ratio in all major organs. Phytosterol pre-treatment as in the P+CCl4 group significantly increased the GSH:GSSG ratio in major organs. The present findings indicate that phytosterols keep tissue glutathione concentration in normal levels which may indicate improving antioxidant status in major organs of the rats treated with carbon tetrachloride.
Keywords: Phytosterol, carbon tetrachloride, glutathione,antioxidant status.